Physical and sexual victimization of persons with severe mental illness seeking care in central and southwestern Uganda - Mpango, Richard Stephen; Ssembajjwe, Wilber; Rukundo, Godfrey Zari; Amanyire, Philip; Birungi, Carol; Kalungi, Allan; Rutakumwa, Rwamahe; Tusiime, Christine; Gadow, Kenneth D.; Patel, Vikram; Nyirenda, Moffat; Kinyanda, Eugene (Frontiers in Public Health, 2023)
This study established the prevalence of physical and sexual victimisation, associated factors and psychosocial consequences of victimisation among 1,201 outpatients with severe mental illness at Butabika and Masaka hospitals in Uganda. Methods: Participants completed structured, standardized and locally translated instruments. Physical and sexual victimisation was assessed using the modified adverse life events module of the European Para-suicide Interview Schedule. We used logistic regression to determine the association between victimisation, the associated factors and psychosocial consequences. Results: The prevalence of physical abuse was 34.1% and that of sexual victimisation was 21.9%. The age group of >=50 years (aOR 1.02;95% CI 0.62 -1.66; P=0.048) was more likely to have suffered physical victimisation, while living in a rural area was protective against physical (aOR 0.59; 95% CI 0.46 -0.76; P=<0.001) and sexual (aOR 0.48, 95% CI 0.35 -0.65; P<0.001) victimisation. High socioeconomic status (SES) (aOR 0.56; 95% CI 0.34 -0.92; P= <0.001) was protective against physical victimisation. Females were more likely to have been sexually victimised (aOR 3.38; 95% CI 2.47 -4.64; P=<0.001), while being a Muslim (aOR 0.60; 95% CI 0.39-0.90; P=0.045) was protective against sexual victimisation. Risky sexual behaviour was a negative outcome associated with physical (aOR 2.19; 95 % CI 1.66 -2.90; P=<0.001) and sexual (aOR 3.09; 95% CI 2.25 -4.23; P<0.001) victimisation. Mental health stigma was a negative outcome associated with physical (aOR 1.03; 95% CI 1.01 -1.05; P<0.001) and sexual (aOR 1.03; 95% CI 1.01-1.05; P= 0.002) victimisation. Poor adherence to oral anti-psychotic medications was a negative outcome associated with physical (aOR 1.51; 95% CI 1.13 -2.00; P=0.006) and sexual (aOR 1.39; 95% CI 0.99 -1.94; P=0.044) victimisation.There is a high burden of physical and sexual victimisation among people with SMI in central Uganda. There is need to put in place and evaluate complex interventions for improving detection and response to abusive experiences within mental health services. Public health practitioners, policymakers, and legislators should act to protect the health and rights of people with SMI in resource poor settings.